Gendered fortunes : divination, precarity, and affect in postsecular Turkey - Korkman, Zeynep K., 1978- (Duke University Press, 2023)
"Gendered Fortunes approaches the proliferating fortunetelling economy of millennial Turkey as an affective window on the gendered contradictions of (post)secularism, Islamist authoritarianism, and neoliberalism. The book ethnographically details how secular Muslim women and LGBTIQ individuals navigate their secular anxieties, gendered vulnerabilities, and economic precarities through divination."--